Quand les tradithérapeutes ouest-africains soignent l’infertilité conjugale à Dakar (Sénégal) : recompositions et dynamiques entrepreneuriales - Sylvain Landry Faye (Anthropologie & Santé)
Over the past years, Dakar has turned into a frequent South-South travel destination. Many African traditional healers settled there with their healing knowledge. This essay attempts to question the effect of their presence in the capital of Senegal on the health supply and demand (in terms of conjugal infertility) and also on the traditional medicine national space. It particularly describes the reason why urban dwellers resort to this medicine in case of infertility, the singularity of therapeutic procedures and the skills put forward as well. It analyses the types of legitimacy mainly used. We reached the conclusions that the free flow of foreign traditional healers in Dakar has given power to pluralism and therapeutic transnationalisation. The latter have earned fame among city-dwellers thanks to their dynamism and omnipresence but also to the popular imaginative universe in favor of them and the singularity of their professional practices as well. Combining biomedical techniques with traditional knowledge appears as a will to gain scientific and universal legitimacy but also emancipation from traditherapy. This “foreign” healers’s approach influences local traditional medicine which, in times past, was subservient to PROMETRA. The individual and entrepreneurial strategies shown by national healers provide information about these important reconfigurations which contribute to the reorganization of traditional medicine in Senegal.